Age, marital status and sexual offences: A “Law Triangle” for women in India - Doshi , Sunil M (Journal of Indian Academy of Forensic Medicine, 2020)
The Indian legislature discriminates women based on age and marital status when quantum of punishment for sexual offences is in question. These two major factors frequently affect the criminalization of an accused by providing windows to escape in cases of sexual offences pertaining to marital relationship. The current ambiguities between the acts and Indian Penal Code in relation to age of consent, marital rape needs to be addressed at earliest. The paper outlines the revolutionary picture of changes in “Age of consent” and describes how multiple marriage acts contradict the content of S.375 IPC. It further argues on the role of the POCSO act with few conflicting verdicts in similar type of cases under the same. The paper reviews the legal aspects of marital rape and discusses how marital rape is still a “permitted offence” even after the recommendations of its deletion by the Justice Verma committee as well as United Nations. It also highlights the parliamentary debates on existence of marital rape. Recent changes in relation to S.375 and S.377 IPC in the context of marital rape are also discussed. It is high time India reconsider these laws that are still popular for their orthodox nature and contradictory content.